Celso Furtado. Culture and film policy - Simis, Anita [UNESP] (Centro Int Estudios Superiores Comunicacion Amer Latina-ciespal, 2016)
This paper aims to understand the gap of cultural policy of the years 1980-1990, called time of transition, and the cultural and political ideas of Celso Furtado, minister of culture from 1986 to 1988. How we move from a forged cultural policy during the dictatorship to another? What are the ideas that guided Celso Furtado in this change to a democratic opening situation? In this sense, the cultural policy implemented by Celso Furtado, particularly the film policy, by presenting itself as a unique landmark, is the primary focus of research.
Keywords: cultural policy; Celso Furtado; cinema; Brazil